1997
DOI: 10.1149/1.1837436
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Force Microscopy Study of Surface Morphology of Zinc‐Iron Electrodeposits

Abstract: Zinc-iron alloys, composed of i (hcp) phase, were electrodeposited on steel substrates from sulfate electrolyte with additions of Sn' ions. The deposit exhibited a morphology of hexagonal columnar crystals and a strong crystallographic texture of (002) planes of i-phase aligned perpendicular to the growth direction. The atomic force microscopy topographical analysis indicates that the hexagonal planes consist of both lateral macro-and numerous nanosize growth

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…29,30 Interplanar spacing (d) for different hkl planes and the axial ratio (c/a) for deposits obtained at different i c values are given in figure 6. Axial ratio value decreased from 1.86 (at 1 Adm −2 ) to 1.66 (at 5 Adm −2 ) or if the iron content was increased as observed by Kondo 31,32 et al This is due to lowering of the value of 'c' and the value of 'a' is almost constant for the hkl planes studied. This showed that the hcp lattice geometry distorted, if the iron content was increased and the probability of substitution of iron along c-axis is more than a-axis, because the linear density along c-axis is lower.…”
Section: Xrd Studiessupporting
confidence: 51%
See 1 more Smart Citation
“…29,30 Interplanar spacing (d) for different hkl planes and the axial ratio (c/a) for deposits obtained at different i c values are given in figure 6. Axial ratio value decreased from 1.86 (at 1 Adm −2 ) to 1.66 (at 5 Adm −2 ) or if the iron content was increased as observed by Kondo 31,32 et al This is due to lowering of the value of 'c' and the value of 'a' is almost constant for the hkl planes studied. This showed that the hcp lattice geometry distorted, if the iron content was increased and the probability of substitution of iron along c-axis is more than a-axis, because the linear density along c-axis is lower.…”
Section: Xrd Studiessupporting
confidence: 51%
“…Very few studies with contrary views, 31,32,38 over this alloy phase structure were reported. The phase structure of this electrodeposited alloy is different from thermally formed alloy phase structure.…”
Section: Phase Structurementioning
confidence: 97%
“…By atomic force microscopy (AFM) studies, the author reported the growth on the hexagonal plates of these hexagonal columnar crystals. [9][10][11] The (00и1) of pure zinc electrodeposit consists of numerous 30 nm granular crystals and the alignments of these granular crystals form macrosteps. 9 For the zinc-iron electrodeposit, the (00и1) consists of fish scale crystals and the edges of these fish scale crystals are the macrosteps.…”
mentioning
confidence: 99%
“…9 For the zinc-iron electrodeposit, the (00и1) consists of fish scale crystals and the edges of these fish scale crystals are the macrosteps. 10 For the zinc-nickel electrodeposit, the (00и1) also consists of fish scale crystals, which are the edges of hexagonal plates. The macrostep heights of the hexagonal plates are 3 nm, which corresponds to about 20 zinc atoms.…”
mentioning
confidence: 99%
“…However, over the last few years the techniques of scanning tunnelling microscopy (STM) and atomic force microscopy (AFM) have proven to be very valuable techniques for the examination of metal deposits. 4,5 The advantage of these techniques with respect to classical techniques for the examination of the structure of metal surfaces (for example, the technique of scanning electron microscopy (SEM)) is the high resolution which is attainable using them. They enable a precise analysis of the topography of a metal surface, i.e., they enable the examination of the submicrotopography of metal surfaces.…”
mentioning
confidence: 99%